Recapitulation of tumor heterogeneity and molecular signatures in a 3D brain cancer model with decreased sensitivity to histone deacetylase inhibition - Smith, Stuart J.; Wilson, Martin; Ward, Jennifer H.; Rahman, Cheryl V.; Peet, Andrew C.; Macarthur, Donald C.; Rose, Felicity R.A.J.; Grundy, Richard G.; Rahman, Ruman (Public Library of Science, 2012)
INTRODUCTION